Faktor-Faktor yang Mempengaruhi Kesiapan Berhenti Merokok pada Perokok Usia Dewasa Awal - Mai Tiza Husna; Dwi Cahya Ashari; Nastiti Naresthi Ramadhini; June Rodhian Dharmariana; Eukaristianica Theofani (Jurnal Ilmu Perilaku, 2020)
The purpose of this study was to determine the factors that affects the readiness to stop smoking in early adult smokers. Factors have analyzed include knowledge, social support, perceived benefits and perceived barriers. Participants of this study were 171 early adult smokers. Non-probability sampling was used as the sampling technique. This study was conducted using quantitative method and data were analyzed by using logistic regression analysis. Results showed that perceived benefits significantly influenced readiness to quit smoking, while knowledge related to risks of smoking, social support and perceived barriers had no effect on readiness to quit smoking. These results also showed that smokers with positive perceived benefits were 1.152 times more ready to quit smoking compared to smokers with negative perceived benefits. Keywords: social support, knowledge, perceived benefits, perceived barriers, readiness to quit smoking